3D Nanostructure of Carbon Nanotubes Decorated Co3O4 Nanowire Arrays for High Performance Supercapacitor Electrode. (1st May 2015) - Ke, Qingqing; Tang, Chunhua; Yang, Zheng-Chun; Zheng, Minrui; Mao, Lu; Liu, Huajun; Wang, John
Highlights: A facile approach is developed to fabricate a newly-designed 3D nanostructure which hybrides free-standing Co3 O4 nanowires and fCNTs for high-performance supercapacitor. The fCNTs-decorated Co3 O4 gives rise to an improved specific capacitance and an excellent cycling stability. The decoration of fCNTs is shown to be an effective approach to improve the electrochemical performance of Co3 O4 nanowire arrays. Abstract: We demonstrate a facile and efficient approach to improve the notoriously poor conductivity of Co3 O4 nanowire arrays by effectively introducing functionalized carbon nanotubes (fCNTs) to generate a 3D nanostructure for high-performance supercapacitor. In this process, the assembly of nanohybrides is driven by the strong electrostatic interaction between the carboxyl groups and amine groups in fCNTs and amine-modified Co3 O4 nanowire arrays. The electrocapacitive behaviors of the newly-designed 3D nanostructure are systematically investigated by cyclic voltammeter and galvanostatic charge-discharge methods. The resultant capacitance value of the fCNTs-decorated Co3 O4 is 559 F g −1, which is 3.5 times higher than that of the pristine Co3 O4 . Such significant improvement is attributed to the enhancement of electrical conductivity by modification of fCNTs, which greatly facilitates an efficient and deep redox reaction of Co3 O4 nanowires. Moreover, an excellent cycling stability is also achieved with the 3D nanohybrid, where the capacitance value can be retained upon 1000 charge-discharge cycles. The decoration of fCNTs is demonstrated to be an effective approach to improve the electrochemical performance of Co3 O4 nanowire arrays. It paves the way of designing oxide-based high-performance supercapacitors by a rational combination of inorganic nanowires with highly conducting CNTs.